The Canadian Optimal Therapy of COPD Trial: Design, Organization and Patient Recruitment. Issue 8 (3rd December 2004) - Aaron, Shawn D; Vandemheen, Katherine; Fergusson, Dean; FitzGerald, Mark; Maltais, Francois; Bourbeau, Jean; Goldstein, Roger; McIvor, Andrew; Balter, Meyer; O'Donnell, Denis
Abstract : BACKGROUND: There are no published studies that have assessed whether adding long-acting beta 2-agonist bronchodilators and/or inhaled steroids to chronic therapy with tiotropium would provide additional clinical benefit to patients with moderate to severe chronic obstructive pulmonary disease (COPD). METHODS: The Canadian Optimal Therapy of COPD Trial is a randomized, prospective, double-blind, placebo-controlled, multicentre trial funded by the Canadian Institutes of Health Research that has been designed to determine which combination of inhaled medications will most effectively prevent exacerbations and optimize disease-specific quality of life in patients with COPD. The trial is the first to evolve from the Canadian Thoracic Society Clinical Trials Group. The study will randomize 432 patients with moderate to severe COPD to one of three parallel treatment arms for 52 weeks: tiotropium and fluticasone/salmeterol; tiotropium and salmeterol; or tiotropium and placebo inhaler. The participants will be allowed to use salbutamol as required throughout the trial period. OUTCOMES: The primary outcome measure is the proportion of patients in the three treatment groups who experienced a respiratory exacerbation within 52 weeks of randomization. Other outcomes that will be assessed over the 52-week trial period will include: changes in disease-specific quality of life and changes in dyspnea, health care use and changes in lung function. A pharmacoeconomic analysis will also be performed to evaluate the cost of these therapies. RESULTS: The study commenced recruitment in October 2003. It is currently operating at 22 centres across Canada and has randomized 137 patients during the first four months of recruitment. Recruitment is scheduled to continue until April 2005 or until 432 patients have been randomized. CONCLUSION: The present randomized, placebo-controlled trial offers a unique opportunity to answer the question, what is the best combination of inhaled medications to use for COPD patients? It is hoped that optimal use of inhaled medications will improve patient health and quality of life, reduce patient respiratory exacerbations, and ultimately, reduce health care resource use.